Matching Into Integrated Plastic Surgery: The Impact of USMLE Step 1 Transition to Pass/Fail: Did the 2019 Predictions Come True in 2024? - Lyndsay R. Boyd, MD; Lawrence O. Lin, MD; Jeffrey E. Janis, MD, FACS (Plastic and Reconstructive Surgery, Global Open)
Background:. The first class of integrated plastic surgery residency applicants with pass/fail (P/F) step 1 assessments occurred during the 2023–2024 Match cycle. This study analyzes the results of a 2024 postmatch survey to program directors (PDs) regarding the impact of the conversion to P/F step 1 scoring and compares the results to the 2019 survey that attempted to predict how this conversion would influence decision-making when it was initially announced. Methods:. A 26-item survey evaluating PDs’ perspectives on applicant characteristics and the application process following P/F step 1 scoring was distributed March 2024. Data were analyzed using summary tables, marginal homogeneity tests, and Mann-Whitney U tests. Results:. Thirty-seven plastic surgery PDs completed the survey (response rate = 46.3%). The top 3 most important metrics for determining applicant interview invitations after step 1 P/F conversion were participation in an away rotation, letters of recommendation, and involvement in research, while ultimately match rank list order emphasized quality of the applicant’s interview. A total of 68.1% of PDs agree that it was more difficult to differentiate applicants without a numerical step 1 score. A total of 51.5% of PDs reported using step 2 clinical knowledge scores to screen applicants. PDs’ opinions on factors influencing the 2023–2024 Match cycle did not significantly change from predictions studied in 2019. Conclusions:. Program directors felt that in the 2023–2024 cycle, it was more difficult to differentiate between applicants, leading to increased emphasis on other characteristics such as away rotations, letters of recommendation, step 2 clinical knowledge scores, and research. There was no difference from what was predicted.